REGISTER ISTILAH BAHASA INGGRIS BIDANG KONSERVASI DAN PRESERVASI SENI WARISAN BUDAYA - Prima Dona Hapsari (Universitas Sebelas Maret, 2021)
Indonesia is rich in cultural heritage which is well-known in the world and most has been recognized by UNESCO. Cultural heritage can be in the form of objects, such as monuments, artefacts, and regions, or no objects, such as tradition, language, and ritual. The study discusses the register of English terms in the realm of conservation and preservation of cultural heritage art. It is aimed at learning English terms in the realm of conservation and preservation of cultural heritage to enrich English vocabulary, finding the form of specific terms in the field of conservation and preservation of cultural heritage, and providing an alphabetical list for terms in the field of conservation and preservation of cultural heritage in English and Indonesian. It is descriptive qualitative research with discourse analysis as a data analysis technique. Data collection techniques used are identification techniques in journal articles and books that discuss the conservation and preservation of cultural heritage. The use of registers in writing out the language in the field of art conservation and preservation, and a glossary of terms arranged systematically and in alphabetical order are urgently needed by academics, conservators, and students. Besides, the English terms in the field of conservation and preservation of the art of cultural heritage are aimed to facilitate students, lecturers, researchers, conservators, and others in understanding and applying them.